Interplant carbon and nitrogen transfers mediated by common arbuscular mycorrhizal networks: beneficial pathways for system functionality - Luo, Xie; Liu, Yining; Li, Siyue; He, Xinhua (Frontiers in Plant Science, 2023)
Arbuscular mycorrhizal fungi (AMF) are ubiquitous in soil and form nutritional symbioses with 80% of vascular plant species, which significantly impact global carbon (C) and nitrogen (N) biogeochemical cycles. Roots of plant individuals are interconnected by AMF hyphae to form common AM networks (CAMNs), which provide pathways for the transfer of C and N from one plant to another, promoting plant coexistence and biodiversity. Despite that stable isotope methodologies (13C, 14C and 15N tracer techniques) have demonstrated CAMNs are an important pathway for the translocation of both C and N, the functioning of CAMNs in ecosystem C and N dynamics remains equivocal. This review systematically synthesizes both laboratory and field evidence in interplant C and N transfer through CAMNs generated through stable isotope methodologies and highlights perspectives on the system functionality of CAMNs with implications for plant coexistence, species diversity and community stability. One-way transfers from donor to recipient plants of 0.02-41% C and 0.04-80% N of recipient C and N have been observed, with the reverse fluxes generally less than 15% of donor C and N. Interplant C and N transfers have practical implications for plant performance, coexistence and biodiversity in both resource-limited and resource-unlimited habitats. Resource competition among coexisting individuals of the same or different species is undoubtedly modified by such C and N transfers. Studying interplant variability in these transfers with 13C and 15N tracer application and natural abundance measurements could address the ecophysiological significance of such CAMNs in sustainable agricultural and natural ecosystems.